The Children’s Oral Health Initiative: An intervention to address the challenges of dental caries in early childhood in Canada’s First Nation and Inuit communities - Mathu-Muju, Kavita R. (Can J Public Health, 2016)
OBJECTIVE: The objective of the Children’s Oral Health Initiative (COHI) is to increase access to preventive oral health services provided to First Nations and Inuit (FN/I) children living on federal reserves and in remote communities. PARTICIPANTS: COHI targets preschool children; 5–7-year-olds; pregnant women; and parents/caregivers in FN/I communities. SETTING: The program was piloted in 2004 by Health Canada and is potentially available to all FN/I communities. However, the community must consent to the program’s implementation and agree to support a community member to be trained as a COHI aide. INTERVENTION: Dental therapists and hygienists screen eligible children, apply fluoride varnish and sealants to children’s teeth, and stabilize active dental caries with glass ionomer. An innovation was the development of a community oral health worker, the COHI Aide. The COHI Aide is a community member who serves as an advocate for preventive oral health in the community and provides instruction to children, parent/caregivers and expectant mothers in preventing dental caries. RESULTS: COHI was piloted in 41 communities in 2004. By 2014, the program had expanded to 320 FN/I communities, which represents 55% of all eligible FN/I communities. In 2012, 23,085 children had received COHI preventive oral health services. CONCLUSION: The results demonstrate COHI’s success as a preventive oral health care delivery model in remote communities. Implementation and delivery of preventive oral health services has been enhanced by the sustained presence of a community-based COHI Aide.